Answer:
x = -6, or x = 7 is the ONLY correct solution of the given equation
![x^(2) + x - 30 = 12.](https://img.qammunity.org/2020/formulas/mathematics/middle-school/77vfgrl33a3mzy5iuk3t01i7kytny6wcvv.png)
Explanation:
Here, the given expression is
![x^(2) + x - 30 = 12.](https://img.qammunity.org/2020/formulas/mathematics/middle-school/77vfgrl33a3mzy5iuk3t01i7kytny6wcvv.png)
or the standard form of the above expression is
![x^(2) + x - 30 - 12 = 0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/z3yapy3ljt183h5zpmoat65ge1zvhqx2mm.png)
or,
![x^(2) + x - 42 = 0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/hqtxs96lvdzy0q2fs432tb55kx8nxawg08.png)
Now, if the equation is of the form
![ax^(2) + bx + c = 0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/mir8vzpyw6zsjohpvkhsz380lcxv6gegp0.png)
Then, b = SUM OF THE ROOTS
and c = PRODUCT OF THE ROOTS
Similarly, in the above expression:
b = 1 = Sum of roots
and c = -42 = Product of the roots.
Here, for x = -6, or x = 7:
Sum of Roots = -6 + 7 = 1
Product of roots = (-6)(7) = -42
Hence, x = -6, or x = 7 is the ONLY correct solution of the given equation.